Intersections between Translation and Book History: Reflections and New Directions. (October 2019) - Colombo, Alice
Abstract : This article identifies points of intersection between the histories of translation and of the book by focusing on the way the two fields have approached textual transmission. After reflecting on the fundamentally complementary aims and methodologies of book and translation historians, it explores the increasingly close relationship between the two histories, and identifies some next steps and possible future areas of intersection. The article also argues that further synergism between translation and book history will make it possible for us to achieve a deeper understanding of the translational and transnational trajectories of texts.